Combined TUNEL and TRAP methods suggest that apoptotic bone cells are inside vacuoles of alveolar bone osteoclasts in young rats - Cerri, Paulo Sérgio [UNESP]; Boabaid, F.; Katchburian, E. (Blackwell Munksgaard, 2003)
Although it is generally accepted that osteoclasts breakdown and resorb bone matrix, the possibility that they may also be able to engulf apoptotic osteoblasts/ lining cells and/or osteocytes remains controversial. Apoptosis of osteoblasts/ lining cells and/or osteocytes and interactions between these cells and osteoclasts are extremely rapid events that are difficult to observe in viva. A suitable in viva model for studying these events is the alveolar bone of young rats because it is continuously. Thus, sections of aldehyde fixed alveolar undergoing intense resorption/remodeling bone of young rats were stained by the combined terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) method and the tartrate-resistant acid phosphatase (TRAP) method for the simultaneous visualization of apoptotic cells and osteoclasts in the same section. The combined TUNEL and TRAP reactions, in the same section, greatly facilitated visualization of relationship between osteoclasts and apoptotic bone cells during alveolar bone remodeling. Our results showed that several TRAP-positive osteoclasts exhibited large vacuoles containing TUNEL positive apoptotic structures, probably derived from osteoblasts/lining cells and/or osteocytes. These results support the idea that alveolar bone osteoclasts are able to internalize dying apoptotic bone cells.
Keywords: alveolar bone; apoptosis; osteoclasts; bone resorption